THE AMBITIOUS ENTREPRENEUR AND HIS ROLE IN STIMULATING CREATIVITY: THE CASE OF TUNISIAN ENTREPRENEURS - Najeh, Hajer; Morched, Salim (Journal of Business And Entrepreneurship, 2022)
This article discusses the role of the ambitious entrepreneur in stimulating creativity and innovation in organizations. Its objective is to build a heuristic model to question the link between the characteristics of the ambitious entrepreneur and creativity. To do this we combine a quantitative study with a qualitative study. An exploratory study of the case of the Tunisian company SOPAL, allowed us to understand the process, which relates the link between the ambition of the entrepreneur and the stimulation of creativity within the organization. We then proceeded with a quantitative study to test our hypotheses on a sample of Tunisian entrepreneurs. The results confirm the impact of an ambitious entrepreneurial profile on stimulating the creativity embodied in technological innovations.